Metabolic equivalents intensity thresholds for physical activity classification in older adults. - Leal-Martín, Javier; Muñoz-Muñoz, Miguel; Sierra-Ramón, Miguel; Cerezo-Arroyo, Mónica; Gómez-Redondo, Paola; Alegre, Luis M.; Ara, Ignacio; García-García, Francisco José; Mañas, Asier (European Review of Aging & Physical Activity, 2024)
Background: Although the metabolic equivalents (METs) system is a common procedure to quantify the intensity of physical activity in older adults, it remains unclear whether the conventional METs intensity thresholds (CTs) used for this purpose are appropriate in this population. Therefore, this study aimed (i) to derive overall and fitness-specific METs intensity thresholds in older adults ≥ 60 years old (OATs) expressed both in standard METs (VO/3.5 mL O·kg·min) and older adults METs (VO/2.7 mL O·kg·min), and (ii) to compare them with the CTs. Methods: A total of 93 subjects were assessed for cardiorespiratory fitness. Graded exercise test protocols using indirect calorimetry were performed to calculate individual VO and categorize subjects as "very poor/fair" or "good/superior" fitness. Overall and fitness-specific OATs expressed in standard METs (OATs) and METs (OATs) were derived based on the %VO and the ventilatory thresholds (VTs) physical intensity categories. Results: Significantly higher VO, VO at VT and VO at VT (p < 0.001) were obtained in the "good/superior" subgroup compared to the "very poor/fair" fitness subgroup. Accordingly, OATs were approximately 69% higher in individuals with a "good/superior" fitness compared to those with a "very poor/fair" fitness. Furthermore, this study showed that OATs were approximately 21–24% lower than OATs, and 10–22% higher OATs were observed when following the VTs intensity categories (heavy-intensity physical activity [HPA] and severe-intensity physical activity [SPA]) compared to the %VO categories (moderate-intensity physical activity [MPA] and vigorous-intensity physical activity [VPA]). When compared with the CTs, similar or higher OATs and OATs for MPA, and HPA were obtained compared to the conventional MPA threshold (3.0 METs). Conversely, for VPA and SPA, lower, similar, or higher OATs were obtained depending on the METs derivation approach (OATs or OATs) or the intensity categories (VO or VTs), compared to the conventional VPA threshold (6.0 METs). Conclusions: None of the derived OATs were concurrently similar to the CTs, suggesting that fitness-specific METs intensity thresholds adapted to the METs derivation approach should be used in older adults. Trial registration: FenotipAGING (Non-health-care intervention study), PRO-Training (NCT05619250).